Ghana @ 60: Governance and human rights in twenty-first century Africa - Michael Addaney (Pretoria University Law Press (PULP), 2017)
Ghana was the first country in sub-Saharan Africa to gain independence and played a critical role in the political transformation and regional integration in Africa. Over the years, Ghana has transformed from one-party state through military rule to multiparty democracy. Since independence, despite internal challenges, Ghana continues to play a critical transformational role on the African continent. This influence has been reinvigorated since the emergence of the concept of African Renaissance and adoption of the 'African solutions for African problems' mantra in the early 2000s. On 6 March 2017, Ghana celebrated its 60th anniversary of independence from colonial rule. Current circumstances in Ghana and Africa reinforce the argument that democracy and the rule of law are maintained by vigilance and involvement of the people. In this regard, this edited volume audited some of the issues relating to the state of human rights standards and compliance, democratic consolidation and development in Ghana as well as to bring forward how Ghana has contributed to the political, economic, cultural and ideological development in Africa. Through a human rights-based approach to governance and socio-economic development, the book examines the experiences of Ghana, selected experiences of other African countries and the African Union in advancing good governance and human rights over the years, on the journey to attain shared prosperity for all. The book takes stock of major developments in the areas of political and civil rights as well as economic, social and cultural rights in Africa, the changing nature of democratisation, regional integration and pan-Africanism, and the ways in which the African Union policies may impact differently on governance and human rights on the continent.